Observational Analysis of Antineoplastic and Immunomodulating Drug Expenditure in Two Local Health Units in Northern Italy during the Period 2009-2011. Issue 3 (November 2016) - Cerra, Carlo; Dellagiovanna, Mirosa; Migliazza, Simona; Tettamanti, Roberto; Zuliani, Corrado; Ravasio, Roberto; Colombo, Delia; Pitotti, Claudia; Zagni, Emanuela
Background: The past few years, the Italian National Health Service (INHS) has faced the challenge of ensuring sustainable costs for antineoplastic and immunomodulating drugs. The aim of this study was to analyse expenditure trends for these drugs in two Local Health Units during the period 2009-2011. Methods: Data for this retrospective study were derived from the administrative databases of two Local Health Units in Northern Italy. A sample was built up by selecting all patients with at least one antineoplastic and immunomodulating drug prescription between 2009 and 2011. The study evaluated the annual, per capita and per user drug expenditure. The antineoplastic and immunomodulating drug expenditure was also analysed by therapeutic indication. Results: The number of users (annual mean rate: 12.1%) and the antineoplastic and immunomodulating drug expenditure (annual mean rate: 15.7%) were increased in the three-year period. The mean annual per capita cost was €18.40 in the first year (2009), €22.18 in the second year (2010) and €24.23 in the last year (2011). Taking into account the last year of the analysis (2011), monoclonal antibody drugs showed the highest per capita drug spending (€9.36), followed by TNF-alpha inhibitors (€6.61) and tyrosine kinase inhibitors (€5.75). The highest mean annual expenditure was on cancer drugs (€15, 046, 773), followed by rheumatoid arthritis (€3, 596, 925), psoriatic arthritis (€925, 510), ankylosing spondylitis (€626, 050) and psoriasis (€622, 332). Conclusions: Spending on antineoplastic and immunomodulating drugs increased over the three-year period of the analysis and the oncological disease was the main therapeutic indication.